Efficacy of Anti-IL6-Receptor Tocilizumab in Refractory Cystoid Macular Edema of Birdshot Retinochoroidopathy Report of Two Cases and Literature Review. (3rd September 2017) - Calvo-Río, Vanesa; Blanco, Ricardo; Santos-Gómez, Montserrat; Díaz-Valle, David; Pato, Esperanza; Loricera, Javier; González-Vela, María C.; Demetrio-Pablo, Rosalía; Hernández, José L.; González-Gay, Miguel A.
ABSTRACT: Purpose : To evaluate tocilizumab (TCZ) efficacy in severe and refractory birdshot chorioretinopathy (BSCR). Methods : Assessment of BSCR patients refractory to conventional immunosuppressive and anti-TNF-α drugs who underwent TCZ therapy. Results : Two HLA-A29 positive patients (man/37 years and woman/38 years; four affected eyes) with BSCR were studied. They had a chronic bilateral posterior uveitis. Patient 1 had been treated with intraocular and oral corticosteroids, cyclosporine A, and infliximab whereas Patient 2 received intravenous methylprednisolone pulses, cyclosporine A, azathioprine, and adalimumab. At TCZ onset they had macular edema (four eyes); visual acuity (VA) impairment (four eyes); vitritis (one eye); and diffuse angiographic signs of vasculitis (periphlebitis) (two eyes). Improvement of VA and OCT was observed following TCZ therapy in both patients. After a follow-up of 18 months (Patient 1) and 10 months (Patient 2), respectively, a corticosteroid sparing effect without any adverse effects was achieved in both cases. Conclusions : TCZ was effective in two patients with BSCR refractory to anti-TNF-α agents.